Expand and simplify. (x+4)squared

(x+4)²= (x+4)×(x+4)

Use the FOIL method to simplify

F=First (multiply the first number of each expression)
O=Outside (multiply the outside edges of each expression)
I= Inside (multiply the inside edges of each expression)
L= Last (multiply the last number of each expression)

x times x= x²
x times 4= 4x
4 times x= 4x
4 times 4= 16

Add them together, we have: x²+4x+4x+16
We can simplify this by adding like terms

Final expression= x² + 8x + 16

\( (x+4)^2 = x^2 + 2(x)(4) + 4^2.(By-identity) \\ \\ => x^2 + 8x + 16 \)